Excessive Iron Induces Macrophage Dysfunction in the Liver, Causing Adverse Pregnancy Outcomes in Mice - Sayaka Shimazaki; Ren Ozawa; Akari Isobe; Sohei Kuribayashi; Hisataka Iwata; Koumei Shirasuna (Metabolites)
Background: Iron is an important micronutrient under physiological conditions, including pregnancy. On the other hand, excessive iron intake is also associated with adverse pregnancy outcomes. Macrophages are crucial in regulating iron homeostasis and pregnancy conditions. However, the role of macrophages in iron metabolism during pregnancy is unclear. Therefore, we used mouse models to investigate whether maternal iron overload induces pregnancy complications and their interactions with macrophages. Methods and Results: Administration of high-dose iron (iron dextran) by intraperitoneal injection to pregnant mice induced pregnancy complications such as fetal death, but low-dose iron did not affect fetal weight. In the placenta, the amount of iron was significantly increased and levels of macrophages were decreased by iron administration. In the liver, iron administration dramatically increased the amount of iron, with increased inflammatory cytokines tumor necrosis factor-α (TNFα) and interleukin-6. Macrophages were observed to surround deposited iron in the liver. In an in vitro experiment, treatment with iron stimulated TNFα secretion with cell death in macrophages, but not in liver cells. To investigate the importance of macrophages during pregnancy, clodronate liposomes were administered to reduce macrophages in pregnant mice. The macrophage reduction in pregnant mice resulted in an increased absorption rate and fetal growth restriction, together with higher iron accumulation and inflammatory cytokines in the liver. Conclusions: Maternal excess iron may induce inflammatory conditions with macrophage dysfunction in the liver, resulting in pregnancy complications. The reduction in macrophages also induced higher iron levels and adverse effects during pregnancy, suggesting a vicious cycle between excessive iron and macrophage dysfunction during pregnancy.